2020
DOI: 10.1123/jsr.2018-0443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Chronic Stretch Training Program at Different Intensities on Joint and Muscle Mechanical Responses: A Randomized Clinical Trial

Abstract: Context: Stretching intensity is an important variable that can be manipulated with flexibility training. However, there is a lack of evidence regarding this variable and its prescription in stretching programs. Objective: To investigate the effects of 12 weeks of knee flexor static stretching at different intensities on joint and muscle mechanical properties. Design: A randomized clinical trial. Setting: Laboratory. Participants: A total of 14 untrained men were allocated into the low- or high-intensity group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…As we did not investigate the time-course of the changes in these variables, future studies may consider exploring it to identify whether there are differences between HI-SS and LI-SS groups; i.e., whether different intensities influence stretch tolerance and muscle stiffness in different time-courses. Interestingly, our results are in opposition to those of Beltrão et al (2020) and Fukaya et al (2020b), which found no differences between low and high intensities on improving muscle passive properties. However, it is important to note that they analyzed the hamstring muscles, while we analyzed the plantar flexors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As we did not investigate the time-course of the changes in these variables, future studies may consider exploring it to identify whether there are differences between HI-SS and LI-SS groups; i.e., whether different intensities influence stretch tolerance and muscle stiffness in different time-courses. Interestingly, our results are in opposition to those of Beltrão et al (2020) and Fukaya et al (2020b), which found no differences between low and high intensities on improving muscle passive properties. However, it is important to note that they analyzed the hamstring muscles, while we analyzed the plantar flexors.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast to these immediate acute effects, no benefits have been shown for higher intensities following bouts of SS on chronic adaptations (Magnusson et al, 1996;Folpp et al, 2006;Beltrão et al, 2020;Fukaya et al, 2020b). Specifically, Fukaya et al (2020b) investigated two different stretching intensities for 4 weeks (100 vs. 120% of the hamstring muscles maximum tolerable ROM; 1 set of 60 s; 3×/week) and showed similar results on ROM between conditions and no change in passive stiffness in both conditions.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, regional differences seem to occur in the chronically stretched muscle, since a different remodelling was observed between its middle and distal portions (Dix and Eisenberg 1990 ). However, the architectural responses to PST in humans are not clear (Nakamura et al 2012 ; Akagi and Takahashi 2014 ; Konrad and Tilp 2014 ; Blazevich et al 2014 ; Freitas and Mil-Homens 2015 ; Simpson et al 2017 ; Sato et al 2020 ; Beltrão et al 2020 ) and more studies may be required to evaluate the impact of a long-term PST program on muscle architecture (Medeiros and Lima 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…All the retrieved studies applied passive stretching interventions [ 45 52 ], except for that of Halbertsma and Göeken who applied a contract–relax (PNF) protocol [ 53 ]. The interventions had a length of 3 [ 48 ], 4 [ 45 , 46 , 52 , 53 ], 5 [ 51 ], 6 [ 49 ] and 12 weeks [ 47 , 50 ]. Stiffness was assessed in five studies through passive resistance to a stretch [ 45 47 , 49 , 53 ] and in three studies using SWE [ 50 52 ].…”
Section: Resultsmentioning
confidence: 99%